Peculiarities of Writing Research Projects Taking into Account Specificity of Professional Preparation of Speciality «Music Art» - Maryna Mykhas’kova (Pedagogical Discourse, 2013)
Research project as a scientific-practical category has been studied in the article, the kinds and functions of research projects, specificity of writing them on speciality «Music Art» have been analyzed. The attention in the article is paid apart to the directions and reference points of diploma projects on music pedagogics and methods of music education, approximate enumeration of the thematics of research projects on these sciences have been given. The author of the article underlines that scoping of pedagogical, aesthetic, artistic and professional-subject sphere in the process of writing is the necessary element of scientific works of the future teachers of music. These help professionals to solve scientific tasks and display their ability to conduct scientific research, to see professional problems and to apply the ways, methods and modes to overcome them.